Considerações sobre a não-realização da vogal epentética em corpus poético do Português Arcaico - Cangemi, Ana Carolina Freitas Gentil Almeida [UNESP] (2012)
This study has as main aim to discuss the motivation for the non-occurrence of epenthetic vowel at the beginning of the word in the context of word junction in the first hundred Cantigas de Santa Maria (CSM – Afonso X, 1221-1284). Through this work and from a non-explored corpus (especially as for linguistic themes - SNOW, 1987, p. 478-480; MASSINI-CAGLIARI, 2005, p. 24-26), we intended to contribute to reaching a deeper knowledge of Portuguese prosody history in the period of its recognition as an “independent” language in relation to Latin.